Fighting in France - Kay, Ross; Wrenn, Charles L. (Charles Lewis), 1880-1952 (Salt Lake City, UT : Project Gutenberg, 2007)
"Fighting in France" by Ross Kay is a historical account written in the early 20th century. This work chronicles the experiences and valor of soldiers during World War I, focusing particularly on the life of two American twin brothers, Leon and Earl Platt, as they fight in the French army alongside their friend Jacques. The book aims to capture the realities of war without sensationalizing the events, presenting a mix of factual incidents and fictional storytelling. The opening of the book introduces the three main characters as they await battle in the trenches of Champagne, France. Leon and Earl, who enlisted in the French army after being caught in Europe during the outbreak of the war, share their determination and camaraderie with Jacques, a young Frenchman. The trio engages in conversations about the upcoming attack set to take place the following morning, discussing their artillery support and the excitement of combat, while humor and a sense of youthful bravado intermingle with the seriousness of warfare. As they prepare for the conflict, the atmosphere is charged with anticipation, blending humor with the grim realities that lie ahead. (This is an automatically generated summary.)
Release date is 2007-04-05
E-text prepared by Al Haines
Keywords: World War, 1914-1918 -- Juvenile fiction